Toleransi Beragama dalam Pemikiran M. Quraish Shihab: Aktualisasi Nilai Wasathiyyah dalam Konteks Keindonesiaan - Harda Armayanto; Amir Sahidin; Rahmat Kurniawan Siregar (Moderasi : Journal of Islamic Studies, 2026)
Indonesia’s religious plurality requires a concept of tolerance that is not merely normative but also operational for civic life, interreligious coexistence, and digital-era public communication. This article reconstructs M. Quraish Shihab’s thought on religious tolerance and examines its relevance to the Indonesian context. Using qualitative library research and thematic-textual analysis, the study examines Shihab’s primary works on Qur’anic interpretation, wasathiyyah, tolerance, Islam and nationality, and contextual interpretation, then relates them to recent scholarship and Indonesian religious moderation policy. The study finds that Shihab’s religious tolerance rests on five interrelated principles: no coercion in religion, Islam as mercy for all creation, recognition of plurality as divine will, universal ethical-humanitarian values, and contextual interpretation of religious texts. These principles define tolerance as active respect in the social sphere without relativizing theological conviction. In the Indonesian context, Shihab’s thought is relevant for interpreting Pancasila, strengthening interreligious harmony, supporting the national agenda of religious moderation, and responding to digital polarization and religious hate speech. The article contributes to Islamic studies by connecting Qur’anic hermeneutics, wasathiyyah, and Indonesian civic ethics in one analytical framework.